Enhancing the Preparedness of Junior High School Students Through the Establishment of Posyandu Remaja at SMP Islam As-Syarief Karangtengah, Garut - Sitti Syabariyah; Popy Siti Aisyah; Nuni Apriani (Universitas 'Aisyiyah Bandung, 2025)
Adolescence is a critical developmental stage and a national health priority, yet many adolescents, particularly in rural and semi-urban areas, still experience limited access to health education, first-aid literacy, and hygienic practices. This community service initiative aimed to strengthen students’ preparedness and health literacy through structured training on First Aid (P3K) and Clean and Healthy Living Behavior (PHBS) at SMP Islam As-Syarief Karangtengah. The program consisted of educational sessions, demonstrations, and guided discussions. Results showed that students demonstrated strong PHBS knowledge but variable understanding of first-aid wound care, indicating the need for more sustained reinforcement. Although no formal skills assessment was conducted, observational findings suggested increased engagement and growing confidence in basic first-aid concepts. The outcomes highlight the importance of integrating continuous mentorship, periodic refresher training, and stronger collaboration with local health centers to support practical skill development. Schools are encouraged to institutionalize student-led health initiatives, such as adolescent health posts, to ensure sustainability. Future programs should incorporate structured skill assessments and follow-up evaluations to maximize behavioral impact and strengthen school-based health promotion.